Advances in hydroscience. - Chow, Ven Te, 1919-1981 (Academic Press, 1978)
Advances in Hydroscience, Volume 11 -1978 covers topics on the progressive development in water science, including stochastic hydrology, the numerical analysis for hydrodynamic modeling, solid-state hydrology, and subsurface waters. The book presents topics on the theory and examples to model lumped quasi-stochastic and stochastic watershed systems; the progress made in the area of multidimensional numerical modeling of hydrodynamic and water-quality processes in estuary and coastal sea systems; and the physical principles governing the flow of water through snow. The text also includes artic.